DETERMINANTS OF STOCK PRICES IN COAL MINING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Ari Kharisma (International Journal Management and Economic, 2026)
This study aims to analyze the factors affecting stock prices, namely Return on Assets (ROA), Return on Equity (ROE), and Earnings per Share (EPS), in coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX). The research sample consists of 15 companies selected using a purposive sampling technique. The data used are secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id). Parametric tests were employed, and the analytical methods included classical assumption tests, multiple linear regression analysis, the coefficient of determination, and hypothesis testing. The results indicate that ROA, ROE, and EPS have a significant effect on stock prices of coal mining sub-sector companies listed on the IDX during the 2022–2024 period. However, ROA and ROE do not have a significant partial effect, although the combined influence of these three variables remains relevant in determining stock prices.